Static Gratings Modulate Motion After-Effect Duration but Not Direction - George Mather; Andrea Pavan; Rosilari Bellacosa (i-Perception, 2012)
Motion after-effect (MAE) duration was measured after adapting to a dot field drifting transparently over a static grating. Duration was shorter when the grating was oriented orthogonally to the direction of the dot field than when it was oriented parallel to the direction of the dot field. After bi-directional adaptation involving two transparently drifting dot fields, the effect of the grating on MAE duration depended on its orientation with respect to the combined direction of the two fields, not with respect to the direction of the two component directions. On the other hand, changes in grating orientation had no effect on the apparent direction of the MAE from bi-directional adaptation. The effect of grating orientation on MAE duration is consistent with ‘motion-streak’ interactions between motion and form processes, which favour motion signals parallel to local orientation signals. Results obtained with bi-directional adapting stimuli indicate that the interactions occur after the point at which component motion signals are combined to compute pattern direction.